Effect of Polyethylene Glycol on the Synthesis of Tyr-Arg Dipeptide by a-Chymotrypsin in an Organic Medium - Hirano, Y.; Nagao, Y. (Asian Journal of Chemistry, 2013)
The enzymatic peptide synthesis in an organic medium was investigated using a-chymotrypsin in the presence of poly(ethylene glycol) (PEG). The added PEG enhanced the activity of a-chymotrypsin for the synthesis of the peptide Z-Tyr-Arg(NO2)-OBzl.. The activity of a-chymotrypsin in the PEG-added system was higher than in a PEG-free system.